2010
DOI: 10.1007/s11033-010-0188-x
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of ornithine decarboxylase by pcDNA-ODCr inhibits gastric cancer cell growth in vitro

Abstract: Ornithine decarboxylase (ODC), the first rate-limiting enzyme of polyamine biosynthesis, was found to be associated with cell growth, proliferation and transformation. ODC gene expression in gastric cancer was increased and its level was positively correlated with the degree of malignity of gastric mucosa and development of gastric lesions. In order to evaluate the therapeutic effects of antisense RNA of ODC on gastric cancer, an antisense RNA of ODC expressing plasmid pcDNA-ODCr which delivered a 120 bp fragm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Conversely, there is convincing evidence that a low level of ODC activity reduces carcinogenesis [34]. There are few reports of utilizing RNAi to downregulate ODC in various cancers [35,36].…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, there is convincing evidence that a low level of ODC activity reduces carcinogenesis [34]. There are few reports of utilizing RNAi to downregulate ODC in various cancers [35,36].…”
Section: Discussionmentioning
confidence: 99%
“…The molecular dysregulation of the ODC1 gene could alter its expression patterns and leads to overexpression in cancer cells. Studies have revealed that ODC downregulation and activity decline could be associated with the reduced growth of cancer cells (6,7). The current chemical drugs against cancer cells are primarily ineffective and associated with several unwanted side effects.…”
Section: Introductionmentioning
confidence: 99%